Public water supply in Lagos State, Nigeria: Review of importance and challenges, status and concerns and pragmatic solutions - Isaac Idowu Balogun; Adebayo Olatunbosun Sojobi; Emmanuel Galkaye (Cogent Engineering, 2017)
The challenges faced in public water supply in most cities and developing countries are increasing population size, poor operational efficiency of existing waterworks, leakages, low reticulation coverage and poor cost-recovery. Our study revealed variation in the public water-supply-demand gap estimates under low, middle and high population growth rate scenarios. Under a largely urbanized evolution of the LGAs, Lagos State faces an imminent critical water shortage if pragmatic steps are not taken to bridge the public water supply-demand gap. Pragmatic solutions recommended include strategic planning and implementation of new waterworks, improved operational efficiency of existing waterworks, improved reticulation and appropriate cost-recovery.